The Art of Selling Beauty: Analyzing Persuasive Strategies and Speech Acts in Social Media Cosmetics Advertising - Saad, Israa Talib; Ismael, Ayat Adnan (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Advertising represents the principle of persuasion across various contexts, with its primary aim being to attract consumers' interest in specific products or services and ultimately prompt them to make a purchase. To achieve this, advertisers skillfully employ language to engage consumers, often appealing to their desires, emotions, and needs. This study investigates the persuasive strategies and speech acts used in cosmetics advertisements targeting (young) women, particularly on social media platforms: Instagram and Facebook. By analyzing advertisements from well-known brands like Nawras Sattar, Vivian Cream, Huda Beauty, and VË, the research explores how persuasion is constructed through rhetorical strategies—namely ethos, pathos, and logos—to influence consumer’s behavior. Additionally, the study identifies and analyzes various speech acts—assertive, directive, expressive, and commissive—to examine how language functions not only to inform but also to influence and motivate consumers. The research is organized into three sections. The first section emphasizes the significance of persuasive language in cosmetics advertising and outlines the research questions, objectives, hypotheses, and methodology. The second section presents a brief literature review covering the concepts of persuasion, persuasive strategies, advertisements, pragmatics, and speech act theory. The third section offers a practical analysis of selected social media advertisements based on Lucas’s (2009) model of rhetorical strategies and Searle’s (1969) classification of speech acts, illustrating how influencers and brands employ persuasive appeals and speech acts to promote their products. The findings underscore the substantial impact of social media advertising on consumer’s behavior and highlight the importance of strategic communication in digital marketing. Ultimately, the study demonstrates the effectiveness of persuasive language in online advertising and its pivotal role in shaping consumer decisions.